Local and landscape contrasts of the occurrence of native and invasive marmosets in the Atlantic forest biome - Gestich, Carla Cristina; de Souza, Geanne Conceição; Rosa, Clarissa; Passamani, Marcelo; Hasui, Érica; da Cunha, Rogério Grassetto Teixeira (Biodiversity and conservation, 2023)
Habitat loss, fragmentation and invasive species are the major causes of biodiversity loss. In the Atlantic Forest, Callithrix aurita is threatened by habitat modification and the invasion of Callithrix jacchus . We evaluated how landscape variables and a local one, the distance to the roads, influence the presence of the native and invasive species within the distribution range of the native. For that, we retrieved data on the presence of C. aurita and C. jacchus from published papers. Comparing species, C. aurita occurs in higher altitudes and lesser urbanized areas than C. jacchus . In presence modeling, the probability of presence of the native C. aurita was higher within deforested landscapes with intense road traffic, while the presence of the invasive species, C. jacchus , was increased in urbanized areas, mostly in non-mountainous terrain, confirming its generalist habits. If such results are not related to biased detectability, C. aurita are living in suboptimal areas, and probably should be more affected by the presence of invasive species. These opposite characteristics of the species highlighted some regions in which conservation measures should be guided, where C. aurita is probably more present and the negative influence of C. jacchus is still limited.